Foreign price shocks and inflation targeting: Effects on income and inflation inequality - Lilian Rolim; Nathalie Marins (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
Foreign price shocks have significant effects on functional income distribution and on inflation inequality. By increasing prices in domestic currency that are linked to foreign prices, they increase the profit share in some sectors and reduce real wages, in particular of workers whose consumption basket is more sensitive to the price of certain goods (e.g. food prices for low-wage workers). Based on the conflicting-claims inflation literature, we propose a new extension to this framework by incorporating worker's heterogeneity (in terms of nominal income and consumption patterns) in an open economy model with an inflation-targeting regime. We investigate the impacts of foreign price shocks on income and inflation inequality and analyze how monetary policy influences these outcomes. Our simulation results indicate that a positive foreign price shock increases the profit share and the within-workers inequality (in real terms), since low-wage workers are more affected by these shocks. Yet, such effects are mediated by the strength of the monetary policy's transmission channels (domestic economic activity or nominal exchange rate), indicating that the monetary authority response may exacerbate or attenuate these distributive effects.
Keywords: D3; E12; E31; F41; 330; inflation; inequality; monetary policy; foreign shocks; transmission mechanisms